Gas phase adsorption of ammonia using nano TiO2-activated carbon composites – Effect of TiO2 loading and composite characterization. Issue 6 (December 2017) - Rezaei, Ebrahim; Azar, Ruth; Nemati, Mehdi; Predicala, Bernardo
Highlights: Addition of TiO2 enhanced ammonia adsorption capacity of AC substantially. Sol-gel method resulted in deposition of TiO2 nano-particles of 2–10 nm The optimum loading of TiO2 in TiO2 -AC composite was 30%. Ammonia adsorption capacity of TiO2 -AC (30%) was superior to commercial TiO2 . Size of TiO2 nano-particles was a crucial factor for adsorption of ammonia. Abstract: TiO2 -AC composites with different TiO2 loadings were synthesized by sol-gel method and evaluated for adsorption of gaseous ammonia using a continuous flow packed-bed column. The titanium phase in the TiO2 -AC composites was identified as anatase using X-ray diffraction (XRD). The equilibrium adsorption capacity of AC at room temperature (22 °C) increased from 2.48 to 3.22, 5.48, 7.07, and 7.73 mg NH3 g −1 by 10, 20, 30, and 40% TiO2 loadings, respectively. This enhanced capacity originated from the addition of Lewis acid sites (TiO2 nano-particles) to the porous structure of AC. Using transmission electron microscopy (TEM), the size of TiO2 nano-particles were determined as 2–10 nm. Scanning electron microscopy (SEM) showed significant accumulation of TiO2 on the external surface of AC at loadings higher than 30%. Surface characterization and room temperature adsorption capacities singled out the optimum TiO2 loading as 30%. The ammonia adsorption capacity of TiO2 nano-particles in TiO2 -AC (30%) composite was higher than that of commercial TiO2 nano-particles (40 nm), due to the smaller size of TiO2 nano-particles deposited on AC. The addition of TiO2 to AC changed the multilayer adsorption of ammonia to a monolayer adsorption. The TiO2 -AC composites had better performance when compared to the reported values for AC composites with oxide of other metals such as Fe, Co, Cr, Mo, and W. The Langmuir-Freundlich expression accurately described the TiO2 -AC (30%) adsorption isotherms developed for ammonia concentrations in the range of 50–500 ppmv and temperatures in the range of 22–280 °C.